1975
DOI: 10.1159/000178668
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tissue Culture of Normal Adult Human Decapsulated Adrenal Cortex: Radioautographic Studies on the Metabolic Effects of ACTH<sub>1-2</sub><sub>4</sub>

Abstract: ACTH-deprived primary normal adult human adrenocortical cells on the 23rd day in vitro were found to lack any DNA synthetic and proliferative activity, but incorporated uridine-3H and l-leucine-3H actively. In cortical cells of the same age treated for 2 and 7 days with ACTH1-24 (3 X 10-6M) the incorporation of the precursors for RNA and DNA synthesis and the cell proliferation were found to be markedly stimulated. The apparent uptake of leucine-3H was ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The same effects could be shown in primary bovine and human adrenal cell cultures [12 ± 14]. However, there were also contradictory results ± Armato et al observed an increase in DNA synthesis in human adrenocortical primary cultures [15] and an increased shift of these cells into the S and M phases of the cell cycle, resulting in enhanced proliferation [16]. Because all experiments at that time had been performed in the presence of fetal calf serum, Menapace et al investigated the effects of ACTH 1-24 on rabbit adrenocortical primary cells in a synthetic medium and found a stimulatory effect on DNA synthesis and cell proliferation [17].…”
mentioning
confidence: 67%
“…The same effects could be shown in primary bovine and human adrenal cell cultures [12 ± 14]. However, there were also contradictory results ± Armato et al observed an increase in DNA synthesis in human adrenocortical primary cultures [15] and an increased shift of these cells into the S and M phases of the cell cycle, resulting in enhanced proliferation [16]. Because all experiments at that time had been performed in the presence of fetal calf serum, Menapace et al investigated the effects of ACTH 1-24 on rabbit adrenocortical primary cells in a synthetic medium and found a stimulatory effect on DNA synthesis and cell proliferation [17].…”
mentioning
confidence: 67%